Comparative analysis of kill probability one of the main features of Air Defense Integrated Systems - Vasile SANDRU; Mircea BOSCOIANU (INCAS Bulletin, 2014)
The combat features of the Ground Based Air Defence Systems represent the potential of search, discovery, indicate, combat and destruction of the enemy's air assets and the ability to manoeuvre of forces and combat means, for the purpose of capturing the enemy's airspace and avoid actions and attack to defend objectives (of troops) assigned in the area of responsibility tacking into account the conditions established by the mission. The paper is focused on a comparative study on the possibilities of target destruction of the Air Air Defence Systems (antiaircraft artillery and Surface-To-Air Missiles). Two situations were chosen: for the first case, related to S1, S2 and S3, we’ve assumed the presence of a flying target describing a uniform rectilinear trajectory both in the presence and in the absence of the enemy’s electronic jamming. For the second case concerning S4 we’ve assumed that the target changed its angle of flight.